The Implications of Lignocellulosic Biomass Chemical Composition for the Production of Advanced Biofuels. (11th February 2014) - Sorek, Nadav; Yeats, Trevor H.; Szemenyei, Heidi; Youngs, Heather; Somerville, Chris R.
Abstract : The majority of terrestrial biomass accumulates as plant cell walls, the main structural component of leaves, stems, roots, fruits, and seeds. The main constituents of plant cell walls are lignin and polysaccharides, which can be transformed into liquid fuel molecules through chemical transformation or microbial fermentation. Because of the large scale of demand for fuel, it is essential that biomass-to-fuel conversion processes maximize conservation of energy in the products. Here, we summarize some of the challenges posed to these processes by the chemical complexity of plant cell walls.